World Society Divided: Divergent Trends in State Responses to Sexual Minorities and Their Reflection in Public Attitudes. (7th April 2018) - Hadler, Markus; Symons, Jonathan
Abstract: This paper extends existing world society literature on the international diffusion of norms by examining divergence in world society. First, we identify polarizing trends in national regulation of homosexuality. Since 2005, the dominant post-WWII global trend toward liberalization has been challenged by a countervailing trend in which some countries have adopted more repressive laws regulating homosexuality. Second, we seek to identify whether states' alignment with either liberal or conservative world models influences public opinion. Analyzing three waves of data on public acceptance of homosexuality from the Pew Global Attitudes Survey between 2002 and 2013, we find that world public opinion concerning homosexuality has become increasingly polarized and that public opinion is embedded in broader institutional structures. Characteristics including education, age, and religious affiliation (and the lack of thereof) also affect individual acceptance of homosexuality, whereas the influence of age and education has diminished over time.